An Object Oriented Approach to Model Reusability - Manuel, Laura; Tirado-Ramos, Alfredo; Castanon Puga, Manuel (Proceedings / IEEE International Symposium on Computer-Based Medical Systems, 2017)
Sexual contact networks for disease transmission have been used extensively with HIV and provide valuable insight into the way the disease spreads through a population. These computationally intensive models often suffer from lack of reusability which makes them expensive to create, use, and escalate. We take an innovated approach to build an HIV transmission model designed for expansion and reusability, and add novel functionality for model realism.